Distribution of phytoplankton pigments in the Nethravathi estuary - Gowda, G; Gupta, T R C; Rajesh, K M; Gowda, H; Lingadhal, C; Ramesh, A M (Indian Journal of Fisheries, 2011)
Distribution of phytoplankton pigments were studied during Feb. 1993 - May 1994 in the Nethravathi estuary, Mangalore. Chlorophyll a, b and c varied between 1.18 - 11.35 mg/m3, 0.12 - 14.88 mg/m3 and 0.08 - 25.82 mg/m3 respectively with higher concentrations during May, June - July and Nov. - Dec. The carotenoids varied between 0.01 and 16.31 mg/m3 with peaks during Oct. - Nov. and March - April. Variation of pigments are due to temperature, salinity and nutrients in the Nethravathi estuary.